Evaluating the economic benefits of moving from a single building to a community approach for sustainable urban redevelopment: Lisbon neighborhood case study. (1st July 2021) - Pedro, Joana; Reis, Anabela; Silva, Carlos; Pinheiro, Manuel Duarte
Abstract: Previous studies demonstrated how urban sustainability assessment systems can support the decision-making process to enhance the sustainability performance of an existing urban area. Nevertheless, although these systems were conceived to evaluate environmental, social, and economic dimensions of sustainability, the economic dimension is still underrepresented, particularly in terms of alternative project solutions' economic feasibility. Therefore, this paper used a neighborhood redevelopment project in Lisbon (Portugal) to propose the economic evaluation of alternative sustainable solutions from single buildings to fully integrated community strategies. For this purpose, it estimated and compared the net present value, the internal rate of return, and the payback time of three alternative renovation strategies: creation of green space areas for urban agriculture; installation of photovoltaic systems; and installation of water harvesting systems. The results showed that community strategies can maximize the economic benefits over time by taking advantage of scale economies and synergies between buildings. In addition, the paper highlighted the possible economic benefits of combining alternative renovation strategies. Finally, it discussed policy and regulatory considerations, providing recommendations for future versions of urban sustainability assessment systems. Highlights: The paper compared sustainable building renovation strategies versus community ones. It focused on three alternative solutions: green spaces; photovoltaic, and water harvesting systems. Community strategies potentiated economies of scale and synergies between buildings.